Highlighting human as a servant to God in 'Hari yang Bergelar Kematian' short story: based on takmilah theory / Mohd Haniff Mohammad Yusoff - Mohammad Yusoff, Mohd Haniff (Universiti Teknologi MARA, Perlis, 2019)
This study attempts to identify and deconstruct the aesthetics of a short story based on the principles advocated in the Takmilah theory. Short story is a genre of creative writing that writers choose to convey their thoughts in a shorter medium of delivery than a novel. Islamic narratives raise the question of divinity as well as the relationship between man and the Creator and the relationship between man and man. A short story entitled 'Hari yang Bergelar Kematian' from Juri Durabi was selected as the research data in this study. This short story was published in Mingguan Malaysia newspaper on March 12, 2017 and has been recognized as one of the winners of Hadiah Sastera Kumpulan Utusan (HSKU) 2017. Takmilah theory outline founded by Shafie Abu Bakar has been selected in this study to achieve the objectives of this study. The findings of the study show that the short story which is entitled 'Hari yang Bergelar Kematian' complies with the principles in Takmilah theory, even highlighting human as a servant to God.